Pemanfaatan media campuran lumpur, kotoran ayam, dan ampas tahu yang difermentasi EM4 untuk budidaya cacing sutra (Tubifex sp.) dengan konsentrasi yang berbeda - Yosua Dedy Patongloan; Henneke Pangkey; Hariyani Sambali; Jeffrie F. Mokolensang; Reiny A. Tumbol; Sammy N.J. Longdong (Universitas Sam Ratulangi, 2023)
The purpose of this study was to determine differences in the growth of silkworm biomass (Tubifex sp.) in mixed media of sludge, chicken manure, fermented tofu dregs with EM-4 solution with different concentrations. This research was conducted at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Sciences, Sam Ratulangi University, Manado. The method used in this study was an experimental method using a completely randomized design (CRD) with 4 treatments, and each treatment had 3 replications. The results showed that the absolute weight gain of silk worms (Tubifex sp.) was highest in treatment medium B which resulted in an average absolute growth of 11.83 grams of biomass, and the best relative growth of silk worms was in treatment B (591.83%). The water quality parameter as supporting data in this study is the temperature of 27.7℃ - 28,4℃, pH 4.7-5.2, and DO 5.9-6.4 mg/l. based on the results of the study it can be concluded that the treatment of tofu dregs fermentation with EM-4 solution at different concentrations for silkworm culture media (Tubifex sp.) had a very significant effect on the absolute growth of silk worms and the relative growth of silk worms. Keywords: biomass, absolute growth, running water system